Three-Dimensional Numerical Simulation of Pyrolysis of Polymethyl Methacrylate under Non-Uniform Radiative Heating - Sun, Yujia (Polymers, 2022)
PMMA material is widely used in the building and household industries, and its pyrolysis behavior is important for fire safety. In real fire conditions, polymethyl methacrylate (PMMA) material will receive non-uniform distributed radiative heat flux from heat sources (such as fire). However, most of the existing work on this subject is limited to one dimensional geometry with uniform heat flux. This paper investigates the heat transfer and pyrolysis mechanism of PMMA material under non-uniform radiative heat flux. A three-dimensional model is developed to this end with a consideration of in-depth radiation and surface heat loss. The results show that temperature and density contours are highly non-uniform inside the solid and there is both a high-temperature core and low-density core beneath the surface. The maximum temperature occurs at a location under the top surface.